HGG-29. DIFFUSE MIDLINE GLIOMA WITH OSSEOUS METASTASES AT DIAGNOSIS: A CASE REPORT. Issue 2 (22nd June 2018) - Belongia, Meghan; Bhatt, Neel; Houser, Kerri; Foy, Andrew; Jarzembowski, Jason; Suchi, Mariko; Kelly, Teresa; Maheshwari, Mohit; Knipstein, Jeffrey
Abstract: INTRODUCTION: High grade glioma with extraneural disease is a rare presentation with a dismal prognosis. We report the case of a pediatric patient who was found to have osseous metastases at diagnosis. CASE: A 15-year-old female presented with paraplegia and urinary retention. In addition, she reported dyspnea on exertion, anxiety, chest pain, back pain, and headaches for 10 days prior to presentation. MR brain and spine demonstrated innumerable intradural lesions causing spinal cord compression, a fourth ventricular lesion, and leptomeningeal seeding throughout the neuraxis. She also had numerous osteoblastic lesions involving the spine, ribs, sternum, pelvic bones, proximal humerus and proximal femurs noted on MR and CT. She underwent a laminectomy for biopsy of the intradural lesion. Histology showed a high grade astrocytic neoplasm consistent with diffuse midline glioma, H3 K27M mutant. Bone and marrow biopsies of the iliac crest revealed metastatic disease. The patient did not receive further adjuvant therapy due to rapid clinical deterioration. She died 13 days following presentation. Autopsy was performed, and no tumor was found in other visceral organs. CONCLUSION: Extraneural metastases of high grade glioma are extremely rare and, when reported, occur mostly after surgical sampling and usually at the time of disease progression. There are only 3 previously reported cases of extraneural metastases at diagnosis, only one of which was in a pediatric patient. H3K27M-mutated diffuse midline glioma carries a poor prognosis, and this case illustrates that this is particularly so when it presents with extraneural disease.